2016
DOI: 10.2147/copd.s99135
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study on management of chronic obstructive pulmonary disease in Hunan Province, the People�s Republic of China

Abstract: BackgroundIn 2009, our study showed an extreme imbalance and disparity in COPD-related health resources allocation at three levels of public hospitals (PHs) in Hunan Province of the People’s Republic of China, especially in second-level PHs. Moreover, most Chinese citizens accept their health care services in first- and second-level PHs for economic and geographical reasons, as well as because of the incomplete transfer system in the health care services. To improve diagnosis and treatment ability of pulmonolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…According to state criterion, all 2nd and 3rd level PHs should be equipped with spirometry. But our previous studies 5 found that the equipment ratio of spirometry were low in Hunan, 2009. Qualitative studies have identi ed some factors that in uence spirometry use in practice: lack of training, lack of time, low remuneration and lack of access to a well-maintained spirometry 6 .…”
Section: Introductionmentioning
confidence: 86%
“…According to state criterion, all 2nd and 3rd level PHs should be equipped with spirometry. But our previous studies 5 found that the equipment ratio of spirometry were low in Hunan, 2009. Qualitative studies have identi ed some factors that in uence spirometry use in practice: lack of training, lack of time, low remuneration and lack of access to a well-maintained spirometry 6 .…”
Section: Introductionmentioning
confidence: 86%